Causal Nexus between the Anamolies in the Crude Oil Price and Stock Market - Hawaldar, Iqbal Thonse; Rajesha, T. M.; Lokesha, Lokesha; Sarea, Adel M. (International Journal of Energy Economics and Policy, 2020)
The paper attempts to examine the causal association between the crude oil price anomalies and stock market returns in the Indian stock market. The study covers nine years starting from 2009 to 2018, and the study includes ten companies in the oil drilling and exploration sectors listed in the BSE SENSEX and CNX NIFTY indexes. We employed correlation tests in determining the relationships amongst the stock market return, crude oil price and market benchmarking indexes. Our study concludes that the oil price shocks is not directly affecting the stock prices of oil-related firms; instead, its indirectly impacting the economy through different channels such as fiscal, trade and price channels. We also suggest the need for future researches in determining the effect of oil price variations on the macroeconomic factors by precisely diagnosing the role of channels mentioned above. Keywords: Oil prices, Stock market, Crude oil price, Emerging Markets, Indian stock market JEL Classifications: G12, G15, Q43 DOI: https://doi.org/10.32479/ijeep.9036